A Shred of Evidence on Theories of Wage Stickiness - Blinder, Alan S.; Choi, Don H. (Quarterly Journal of Economics, 1990)
A small interview survey was undertaken to see how actual wage-setters would react to the central ideas of several economic theories of wage stickiness. Wage cuts were surprisingly prevalent in recent years, despite the booming economy. The strongest finding was that managers believe that perceptions of fairness play a major motivational role in labor markets and that a “fair” wage policy is a good deal more complicated than simply not cutting wages. We also found substantial evidence for money illusion and against the adverse-selection version of the efficiency wage model.